Early coronary angiography and percutaneous coronary intervention are associated with improved outcomes after out of hospital cardiac arrest. (February 2018) - Jentzer, Jacob C.; Scutella, Michael; Pike, Francis; Fitzgibbon, James; Krehel, Nicholas M; Kowalski, Lindsay; Callaway, Clifton W.; Rittenberger, Jon C.; Reynolds, Joshua C.; Barsness, Gregory W.; Dezfulian, Cameron
Abstract: Aim: Early coronary angiography (CAG) and percutaneous coronary intervention (PCI) are associated with better outcomes in subjects resuscitated from out-of-hospital cardiac arrest (OHCA). We sought to determine the relative contributions of early CAG and PCI to outcomes and adverse events after OHCA. Methods: We analyzed 599 OHCA subjects from a prospective two-center registry. Hospital survival, functional outcomes and adverse events were compared between subjects undergoing early CAG (within 24 h) with or without PCI and subjects not undergoing early CAG. We adjusted for propensity to perform early CAG and PCI and for post-resuscitation illness severity and care. Results: Early CAG subjects had improved rates of hospital survival (56.2% versus 31.0%, OR 2.85 [95% CI 2.04–4.00]; p < 0.0001) and better functional outcomes compared to no early CAG. Early PCI was associated with improved survival compared to early CAG without PCI (65.6% versus 45.5%, OR 2.29 [95% CI 1.41–3.69]; p < 0.001). After multivariate adjustment and propensity matching, early PCI remained significantly associated with improved survival compared with early CAG without PCI and no early CAG, but early CAG without PCI was no longer significantly associated with improved outcome compared with no early CAG. Early CAG and early PCI were not associated with an increase in transfusions or acute kidney injury. Conclusions: Early CAG and PCI are associated with improved survival and functional outcomes after OHCA, but only early PCI was associated with a significant benefit after statistical adjustment. Our analysis supports the performance of immediate CAG to determine the need for PCI in selected patients following resuscitation from OHCA.